Genetic and clinical characteristics of patients with lipoprotein lipase deficiency from Slovenia and Pakistan: case series and systematic literature review - Ain, Quratul; Cevc, Matija; Marusic, Tatiana; Sikonja, Jaka; Sadiq, Fouzia; Sustar, Ursa; Mlinaric, Matej; Kovac, Jernej; Batool, Hijab; Khan, Mohammad Iqbal; Trebusak Podkrajsek, Katarina; Bizjan, Barbara Jenko; et al. (Frontiers in Endocrinology, 2024)
Introduction. Hypertriglyceridemia (HTG) is a complex disorder caused by genetic and environmental factors that frequently results from loss-of-function variants in the gene encoding lipoprotein lipase (LPL).Heterozygous patients have a range of symptoms, while homozygous LPL deficiency presents with severe symptoms including acute pancreatitis, xanthomas, and lipemia retinalis.Methods. We described the clinical characteristics of three Slovenian patients (an 8-year-old female, an 18year-old man, and a 57-year-old female) and one Pakistani patient (a 59-year-old male) with LPL deficiency.We performed next-generation sequencing (NGS) targeting all coding exons and intron-exon boundaries of the LPL gene, and Sanger sequencing for variant confirmation. In addition, we performed a systematic literature review of all cases with three identified variants and described their clinical characteristics.Results. Two Slovenian patients with a heterozygous pathogenic variant NM_000237.3:c.984G>T (p.Met328Ile) were diagnosed within the first three years of life and had triglyceride (TG) values of 16 and 20 mmol/L. An asymptomatic Pakistani patient with TG values of 36.8 mmol/L until the age of 44 years, was identified as heterozygous for a pathogenic variant NM_000237.3:c.724G>A (p.Asp242Asn). His TG levels dropped to 12.7 mmol/L on dietary modifications and by using fibrates. A Slovenian patient who first suffered from pancreatitis at the age of 18 years with a TG value of 34 mmol/L was found to be homozygous for NM_000237.3:c.337T>C (p.Trp113Arg).Patients with LPL deficiency had high TG levels at diagnosis. Homozygous patients had worse outcomes. Good diet and medication compliance can reduce severity.